Altered regulation of serum lysosomal acid hydrolase activities in Parkinson's disease: A potential peripheral biomarker?. (April 2019) - Niimi, Yoshiki; Ito, Shinji; Mizutani, Yasuaki; Murate, Kenichiro; Shima, Sayuri; Ueda, Akihiro; Satake, Wataru; Hattori, Nobutaka; Toda, Tatsushi; Mutoh, Tatsuro
Abstract: Introduction: Recent studies have indicated that lysosomal dysfunction contributes to the development of idiopathic Parkinson's disease (PD). It is uncertain whether dysregulation of serum lysosomal acid hydrolase activity exists in sporadic PD patients compared with normal controls (NCs) and parkinsonian syndrome (PS) patients. Methods: Sporadic PD patients without GBA1 mutations (n = 68) were matched with normal controls (n = 45), and parkinsonian syndrome patients (n = 32) in terms of family history, age, and sex. We measured the activities of lysosomal enzymes, α-galactosidase, β-galactosidase, and β-hexosaminidase and examined the possible correlations between lysosomal acid hydrolase activities with age in NCs, PD, and PS patients. Results: β-Galactosidase activity was significantly higher in the PD and PS than in the NC group ( P  < 0.001). The β-galactosidase to α-galactosidase and β-hexosaminidase to β-galactosidase activity ratios were more useful for distinguishing PD and PS patients from NCs ( P  < 0.0001). Furthermore, α-galactosidase activity was significantly higher in PS patients than both PD and NC groups (p = 0.04). β-Galactosidase and α-galactosidase activities exhibited a statistically significant negative correlation with age in NCs, and β-hexosaminidase activity showed a positive correlation with age in PS. However, PD patients did not show any of these correlations. Conclusion: Our results suggest the presence of an unknown regulatory mechanism(s) of serum acid hydrolase activities with aging in the normal population and abnormalities in their regulation in PD and PS patients. However, the pattern of dysregulation in these two groups is different. Thus, serum lysosomal acid hydrolase activity can be used as a peripheral biomarker for PD. Highlights: All serum lysosomal hydrolases activities were not correlated with age in PD. α-galactosidase and β-galactosidase activities in normal controls and b-hexosaminidase in PS were correlated with age. In PD, serum β-galactosidase activity is higher than in normal controls, and α-galactosidase activity is lower than in PS. Abnormal serum enzymatic activity may reflect decrements in the peripheral trafficking and metabolism of lysosomal enzymes.